Beyond the Screen: Socialization, Community Building, and Interpersonal Connectivity in Bangladesh Through Video Games - Hossain, Syed Arman; Fahad, Abdullah Al (CyberOrient, 2024)
This article explores the intricate dynamics of video gaming among the youth of Dhaka, Bangladesh, exploring its profound influence on socialization and community building within the framework of theories such as the Theory of Attainment, Imagined Community, User and Gratification Theory, and Bourdieu's concept of “social capital.” Through a comprehensive blend of digital and autoethnographic methods, the research unveils how gaming transcends its solitary image to emerge as a potent cultural force in Bangladeshi society. The findings underscore the pivotal role of gaming in forging social bonds and nurturing communities, both in virtual realms and physical spaces. Gamers actively engage in collaboration, strategic planning, and the exchange of experiences, mirroring the dynamics of real‐world social networks. Despite concerns regarding addiction, the article illuminates the impact of video games on social cohesion among the youth demographic. Furthermore, it inquires into gaming culture's remarkable resilience in the face of societal norms and regulatory challenges, shedding light on the adaptive strategies employed by gamers to navigate and thrive in diverse contexts. By exploring the intricate interplay between virtual and real‐life experiences, this research contributes to a deeper understanding of how video games shape socialization among urban youth in the ever‐evolving landscape of Bangladesh.